Ontology of Meaning in Life and Self-Transcendence: A Phenomenological-Philosophical Review of Adaptation Experiences among Hemodialysis Patients - Septiani Tri Sutrisni; Priyanto Priyanto (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Patients with chronic kidney disease (CKD) undergoing hemodialysis face prolonged biopsychosocial and existential burdens due to their lifelong dependence on renal replacement therapy. Amid physical limitations, changes in social roles, and the constant threat of death, many patients actually rediscover the meaning of life through processes of self-transcendence, spirituality, and existential adaptation. This article presents a narrative review to explore how the ontology of life’s meaning and self-transcendence is shaped within the phenomenological experiences of hemodialysis patients. A comprehensive literature search was conducted across three main databases: PubMed, Scopus, and SpringerLink, utilizing the Population, Concept, Context (PCC) framework supplemented by a PRISMA flow diagram. Given the exploratory nature of this narrative review, formal methodological quality appraisal (e.g., JBI Critical Appraisal Tools) was not applied. Fifteen key articles published between 2022 and 2026, employing qualitative and phenomenological designs, were analyzed thematically. The results revealed four major themes: biographical disruption and existential alienation; spirituality and religious coping as anchors of meaning; self-transcendence through altruism and hope; and the paradox of time and long-term psychosocial adaptation. The discussion situates the findings within the frameworks of Heidegger’s phenomenology and Frankl’s logotherapy, demonstrating that the meaning of life for hemodialysis patients constitutes an ontological reconstruction of self-existence in the face of bodily limitations and clinical time. The conclusion emphasizes the need for a nursing approach oriented toward strengthening the spiritual-existential dimension.